Structure-function analysis of yeast mRNA cap methyltransferase and high-copy suppression of conditional mutants by AdoMet synthase and the ubiquitin conjugating enzyme Cdc34p. - Schwer, B (2000)
Here we present a genetic analysis of the yeast cap-methylating enzyme Abd1p. To identify individual amino acids required for Abd1p function, we introduced alanine mutations at 35 positions of the 436-amino acid yeast protein. Two new recessive lethal mutations, F256A and Y330A, were identified. Alleles F256L and Y256L were viable, suggesting that hydrophobic residues at these positions sufficed for Abd1p function. Conservative mutations of Asp-178 established that an acidic moiety is essential at this position (i.e. , D178E was viable whereas D178N was not). Phe-256, Tyr-330, and Asp-178 are conserved in all known cellular cap methyltransferases. We isolated temperature-sensitive abd1 alleles and found that abd1-ts cells display a rapid shut-off of protein synthesis upon shift to the restrictive temperature, without wholesale reduction in steady-state mRNA levels. These in vivo results are consistent with classical biochemical studies showing a requirement for the cap methyl group in cap-dependent translation. We explored the issue of how cap methylation might be regulated in vivo by conducting a genetic screen for high-copy suppressors of the ts growth defect of abd1 mutants. The identification of the yeast genes SAM2 and SAM1, which encode AdoMet synthase, as abd1 suppressors suggests that Abd1p function can be modulated by changes in the concentration of its substrate AdoMet. We also identified the ubiquitin conjugating enzyme Cdc34p as a high-copy abd1 suppressor. We show that mutations of Cdc34p that affect its ubiquitin conjugation activity or its capacity to interact with the E3-SCF complex abrogate its abd1 suppressor function. Moreover, the growth defect of abd1 mutants is exacerbated by cdc34-2. These findings suggest a novel role for Cdc34p in gene expression and engender a model whereby cap methylation or cap utilization is negatively regulated by a factor that is degraded when Cdc34p is overexpressed.